Nanodeformations of microcapsules: comparing the effects of cross-linking and nanoparticles - Doering, Ulrike; Grigoriev, Dmitry; Riske, Tino; Fery, Andreas; Boeker, Alexander (RSC Advances, 2022)
The mechanical properties of proteinaceous and composite microcapsules loaded with oil were measured by SFM and evaluated using the Reissner model. Comparison of the obtained results reveals significantly higher Young’s moduli of protein capsules due to intermolecular crosslinking. In contrast, conformational restrictions in composite microcapsules inhibit protein crosslinking leading to the reduction of their elasticity.
CRIS-Team Scopus Importer:2023-03-20